Structural Changes in Kidneys of Homeo- and Heterothermal Animals Undergoing Artificial and Natural Hypometabolis - Lomako, Viktoriya V.; Kondakov, Igor I. (Problems of Cryobiology and Cryomedicine, 2017)
N/A Probl Cryobiol Cryomed 2017; 27(1): 81–86